Blue gold : a novel from the Numa files - Cussler, Clive; Kemprecos, Paul. (New York : Pocket Books, 2000)
An investigation into the sudden deaths of rare whales sends National Underwater Marine Agency crew leader Kurt Austin to the Mexican coast, where he and his crew stumble upon a white goddess legend and an eco-extortionist set on controlling the world's fresh-water supply.
Adult
Adult
Keywords: Austin, Kurt (Fictitious character) -- Fiction; Missing persons -- Fiction; Saline water conversion -- Fiction; Terrorism -- Fiction; Water supply -- Fiction; Women scientists -- Fiction; Adventure fiction; Austin, Kurt (Fictional character) -- Fiction; Missing persons -- Fiction; Science fiction; Sea water conversion -- Fiction; Terrorism -- Fiction; Water supply -- Fiction; Women scientists -- Fiction; South America -- Fiction; South America -- Fiction; Adventure stories; Science fiction